EFEITO ACIDIFICANTE DA URÉIA E DO SULFATO DE AMÔNIO EM UM LATOSSOLO VERMELHO ESCURO - Mello, Francisco de A. F. de; Possidio, E. L.; Pereira, J. R.; Araújo, J. P.; Abramof, L.; Costa, O. A. (REVISTA DE AGRICULTURA, 2015)
EFEITO ACIDIFICANTE DA URÉIA E DO SULFATO DE AMÔNIO EM UM LATOSSOLO VERMELHO ESCURO